Comparative study of lipase preparations for enzymatic degumming of sunflower oil - Nosenko, Tamara; Zhupanova, Diana (My University, 2023)
Enzymatic degumming of sunflower oil results in an increase in oil yield compared with water degumming. Degumming with Quara®Boost preparation results in 98 % oil yield, which was 1.5 % higher than in the case of water degumming. Using Lecitase® Ultra and Quara Low P increased oil yield by 1 and 0.5 %, respectively, compared with water degumming. The phospholipid content decreased from 0.4 % in crude oil to 0.2 % after water degumming, meanwhile, the application of enzyme preparations Lecitase® Ultra and Quara Low P reduced the content of phospholipids to 0.08 % and 0.06 %, respectively. The lowest phospholipid (stearoiloleillecitin) content 0.04 % was in the sunflower oil after degumming with phospholipase C (Quara®Boost), which corresponds to 16 mg/kg of phosphorus. The saponification value of sunflower oil degummed with phospholipase C preparation proved the formation of diacylglycerols in oil and was 191.5 mg KOH/g. The highest free fatty acid content in sunflower oil was after degumming with Lecitase® Ultra: the acid value increased from 0.86 mg KOH/g in crude oil to 2.7 mg KOH/g in degumming oil. However, Quara Low P preparation also has phospholipase A1 activity, so, the acid value decreased slightly compared with crude oil. Degumming with Quara®Boost preparation did not affect the free fatty acid content in sunflower oil, and the acid value was even lower than in the oil degummed with water. The peroxide value of sunflower oil was <1 meq O/kg after enzymatic degumming, meanwhile the peroxide value of sunflower oil after water degumming was 2.6 meq O/kg. All oil samples had a similar antioxidative capacity, that was 30-36 % of scavenged DPPH• radical.

Enzymatic degumming of sunflower oil results in an increase in oil yield compared with water degumming. Degumming with Quara®Boost preparation results in 98 % oil yield, which was 1.5 % higher than in the case of water degumming. Using Lecitase® Ultra and Quara Low P increased oil yield by 1 and 0.5 %, respectively, compared with water degumming. The phospholipid content decreased from 0.4 % in crude oil to 0.2 % after water degumming, meanwhile, the application of enzyme preparations Lecitase® Ultra and Quara Low P reduced the content of phospholipids to 0.08 % and 0.06 %, respectively. The lowest phospholipid (stearoiloleillecitin) content 0.04 % was in the sunflower oil after degumming with phospholipase C (Quara®Boost), which corresponds to 16 mg/kg of phosphorus. The saponification value of sunflower oil degummed with phospholipase C preparation proved the formation of diacylglycerols in oil and was 191.5 mg KOH/g. The highest free fatty acid content in sunflower oil was after degumming with Lecitase® Ultra: the acid value increased from 0.86 mg KOH/g in crude oil to 2.7 mg KOH/g in degumming oil. However, Quara Low P preparation also has phospholipase A1 activity, so, the acid value decreased slightly compared with crude oil. Degumming with Quara®Boost preparation did not affect the free fatty acid content in sunflower oil, and the acid value was even lower than in the oil degummed with water. The peroxide value of sunflower oil was <1 meq O/kg after enzymatic degumming, meanwhile the peroxide value of sunflower oil after water degumming was 2.6 meq O/kg. All oil samples had a similar antioxidative capacity, that was 30-36 % of scavenged DPPH• radical.
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; enzyme; degumming; phospholipase; sunflower oil; соняшникова олія; фермент; дегумінг; фосфоліпаза